Cardiac epigenetics: Driving signals to the cardiac epigenome in development and disease. (February 2021) - Robinson, Emma Louise; Anene-Nzelu, Chukwuemeka George; Rosa-Garrido, Manuel; Foo, Roger S.Y.
Abstract: Conrad Waddington's famous illustration of a ball poised at the top of an undulating epigenetic landscape is often evoked when one thinks of epigenetics. Although the original figure was a metaphor for gene regulation during cell fate determination, we now know that epigenetic regulation is important for the homeostasis of every tissue and organ in the body. This is evident in the cardiovascular system, one of the first organs to develop and one whose function is vital to human life. Epigenetic mechanisms are central in regulating transcription and signaling programs that drive cardiovascular disease and development. The epigenome not only instructs cell and context specific gene expression signatures, but also retains "memory" of past events and can pass it down to subsequent generations. Understanding the various input and output signals from the cardiac epigenome is crucial for unraveling the molecular underpinnings of cardiovascular disease and development. This knowledge is useful for patient risk stratification, understanding disease pathophysiology, and identifying novel approaches for cardiac regeneration and therapy. In this special issue, a series of high-quality reviews and original research articles examining the field of cardiac epigenetics will broaden our insights into this fundamental aspect of molecular and cellular cardiology. Topics include DNA methylation, histone modifications, chromatin architecture, transcription factors, and long non-coding RNA biology in the diverse cell types that comprise the cardiovascular system. We hope that our readers will expand their horizons and be challenged to envision innovative strategies to further probe the epigenome and develop diagnostic and therapeutic solutions for cardiovascular pathologies.